2021
DOI: 10.1080/02656736.2021.1941312
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and risk factors of male exertional heatstroke in patients with myocardial injury: an over 10-year retrospective cohort study

Abstract: Background: Heatstrokes are a serious threat to human health, particularly the cardiovascular system. Understanding the clinical features and risk factors related to death in patients with myocardial injury (MI) complicated by heat stroke is crucial. Method: This study included the baseline data of all patients with severe heatstroke between October 2008 and May 2019. Results: Of the 162 patients enrolled, 75 (46.3%) were in the MI group and 87 (53.7%) were in the non-MI group. A significant difference was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Prognostic prediction of severe heatstroke using APACHEII score alone may be biased because this disease is often associated with severe coagulation abnormalities and rhabdomyolysis, which are not included in APACHEII score [ 24 ]. Also, it has been shown that there is no significant difference in blood creatinine and bilirubin between surviving and deceased individuals with severe heatstroke, amid these factors reducing the predictive efficacy [ 23 , 25 ]. Our ROC results showed that combination of NLR and APACHEII score was significantly better for predicting death of severe heatstroke patients than using the two individually.…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic prediction of severe heatstroke using APACHEII score alone may be biased because this disease is often associated with severe coagulation abnormalities and rhabdomyolysis, which are not included in APACHEII score [ 24 ]. Also, it has been shown that there is no significant difference in blood creatinine and bilirubin between surviving and deceased individuals with severe heatstroke, amid these factors reducing the predictive efficacy [ 23 , 25 ]. Our ROC results showed that combination of NLR and APACHEII score was significantly better for predicting death of severe heatstroke patients than using the two individually.…”
Section: Discussionmentioning
confidence: 99%
“…These two factors were retained in the prediction model. Myocardial injury is another feature of severe heatstroke, and it is known to increase the risk of death during the rapid progression of severe heatstroke (5,15). Furthermore, TNI appeared to be an analysis factor for death from severe heatstroke (hazard ratio, 1.223; 95% CI, 1.095–1.367; P < 0.0001), which was consistent with findings from prior studies (16).…”
Section: Discussionmentioning
confidence: 99%
“…The course of severe heat-related illnesses combined with SALI and ALF involves protein denaturation, endotoxin release, thermoregulatory disorder, SIRS, interleukin-1beta (IL-1β) and high-mobility group box 1 (HMGB-1)-induced pyroptosis, leading to massive or submassive hepatocyte necrosis, which ultimately aggravates the conditions of such patients. [20,27,28] The 10%-30% mortality rate of EHS in developing countries is still relatively high, [26,29,30] whereas its mortality rate in developed countries is less than 5%. [20,31] An Indian study has demonstrated that the mortality rate reaches 86% when heat stroke is accompanied by MODS.…”
Section: Discussionmentioning
confidence: 99%